How longtime residents use visual media cues to determine evacuation actions before hurricanes. Issue 2 (28th April 2022) - Armstrong, Cory L.; Hou, Jue; Towery, Nathan
Abstract: This study sought to measure risk perception and behavioral intention in rural and urban communities in Mississippi and Alabama when severe weather strikes. We developed an experiment testing how visual cues and media messages surrounding an impending hurricane could influence an individual's decision-making in the situation. Respondents were selected from six counties on Mississippi and Alabama coastlines and placed into one of three conditions, each of which described a hypothetical "Hurricane Farrah, " which was near landfall nearby. Data were collected on 466 respondents and analysis determined that the live video was least likely to motivate respondents to take evacuation measures.